A RARE CASE OF DOUBLE ADRENOCORTICOTROPIC HORMONE-SECRETING PITUITARY ADENOMA - A, Ida Ilyani; WH, Kang; AW, Norasyikin; T, Jegan; BH, Soon; GC, Tan; YP, Wong; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION When distinct pituitary hypersecretory manifestations coexist, the differential diagnoses include plurihormonal or multiple pituitary adenomas. We describe a rare case of Cushing’s disease and central diabetes insipidus caused by two non-contiguous pituitary adenomas, one located within the anterior pituitary and the other in the infundibulum. CASE A 14-year-old female presented with unexplained weight gain, central obesity, hirsutism, polyuria and polydipsia. Hormonal studies indicated Cushing’s disease, and magnetic resonance imaging showed a small focal area of delayed enhancement in the right pituitary gland. While other anterior pituitary hormonal tests were negative, osmolality and water deprivation test confirmed central diabetes insipidus. Endoscopic transsphenoidal surgery revealed 2 lesions containing cheesy-like material at the posterior part of the anterior pituitary and another compressing the infundibulum. The 2 clearly separated pituitary adenomas identified in the same gland were completely resected. Immunohistochemistry and pathology revealed that the double adenomas were positive for adrenocorticotropic hormone (ACTH), thyroid stimulating hormone, growth hormone, luteinising hormone, prolactin and follicle stimulating hormone. Postoperatively, the levels of ACTH and cortisol decreased rapidly. However, she developed panhypopituitarism with persistent diabetes insipidus, requiring hormonal replacement therapy. Multiple pituitary adenomas (MPA) are defined as 2 or more immunocytochemically and/or morphologically distinct tumours that are detected in only 0.37 to 2.6% of surgical specimens and in 1.6 to 3.3% of Cushing’s disease patients. Our patient is the youngest reported patient to our knowledge so far and is considerably rare, due to the presence of a second pituitary adenoma in the same gland detected only intraoperatively and not radiologically, isolated ACTH-secreting tumours, and clinical presentation of diabetes insipidus. CONCLUSION The coexistence of double adenomas can pose diagnostic and management challenges for the pituitary neuroendocrine team and is a common cause for surgical failure. Intraoperative evaluation is important in the identification of multiple pituitary adenomas in a patient presenting with multiple secretory manifestations.